2018
DOI: 10.1177/1359105318785697
|View full text |Cite
|
Sign up to set email alerts
|

Coping with trauma and adversity among Palestinians in the Gaza Strip: A qualitative, culture-informed analysis

Abstract: In this article, we propose that coping is not only an individual property but also a structural feature. Coping shapes what is referred to in social network theory as multiplex networks, which are based on relations with multiple functions, values and meanings. Focus groups with adult Palestinians were held and content analysed. Five main coping strategies were identified: (a) creating cultural and religious meaning; (b) individualism to collectivism; (c) normalization and habituation; (d) belonging, acceptan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 65 publications
(83 reference statements)
1
24
0
Order By: Relevance
“…Afana, Pedersen, Ronsbo, and Kirmayer (2010) found that various idioms of distress used by Palestinians living in the Gaza Strip were linked to their social context: assabiah referred to nervousness, anxious feelings, or jitteriness; qalaq described as being anxious or apprehensive ‐ a state of fear of the future and of the unknown; azma nafsiah described as a psychological crisis because of the continuous daily environmental stressors experienced; azamat (psychological crises); dagt nafsi referred to psychological pressure in relation to repetitive and cumulative daily stressors experienced as overwhelming and hindering day‐to‐day activities; sarih al fiker (absent minded), whereby there is no psychological comfort; araq refers to interruptions in or inability to sleep, also used to describe the experience of thinking about their unknown and insecure future; and kaufa could be associated with various physical symptoms such as fever, headache and general fatigue. In a later study in the Gaza Strip with Palestinians, Afana and colleagues (Afana, Tremblay, Ghannam, Ronsbo, & Veronese, 2018) found further idioms and expressions of distress, which included: fear (khoufa); sadness (hazeen); irritability (arak nafsi); and psychological persecution (idehad nafsi).…”
Section: Introductionmentioning
confidence: 96%
“…Afana, Pedersen, Ronsbo, and Kirmayer (2010) found that various idioms of distress used by Palestinians living in the Gaza Strip were linked to their social context: assabiah referred to nervousness, anxious feelings, or jitteriness; qalaq described as being anxious or apprehensive ‐ a state of fear of the future and of the unknown; azma nafsiah described as a psychological crisis because of the continuous daily environmental stressors experienced; azamat (psychological crises); dagt nafsi referred to psychological pressure in relation to repetitive and cumulative daily stressors experienced as overwhelming and hindering day‐to‐day activities; sarih al fiker (absent minded), whereby there is no psychological comfort; araq refers to interruptions in or inability to sleep, also used to describe the experience of thinking about their unknown and insecure future; and kaufa could be associated with various physical symptoms such as fever, headache and general fatigue. In a later study in the Gaza Strip with Palestinians, Afana and colleagues (Afana, Tremblay, Ghannam, Ronsbo, & Veronese, 2018) found further idioms and expressions of distress, which included: fear (khoufa); sadness (hazeen); irritability (arak nafsi); and psychological persecution (idehad nafsi).…”
Section: Introductionmentioning
confidence: 96%
“…Enhanced SOC can in turn help practitioners to deploy their GRR or coping strategies. This will ultimately lead to a sense of growth and resilience, albeit in settings characterized by intractable instability (Afana et al, 2018;.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, even after accounting for spiritual coping and ethnic identity, results remained significant, suggesting that additional components of the ethnicity construct are impacting resilience scores. This is also conversant with the small but growing body of work focusing on cultural contributors to resilience (i.e., Marie et al, 2016; Afana et al, 2018). Given that, future research should focus on identifying those additional components of the ethnicity construct and teasing out their impact on psychological resilience.…”
Section: Discussionmentioning
confidence: 99%